Bottom-up processing of PbTe-PbS thermoelectric nanocomposites. (1st January 2014) - Ortega, Silvia; Ibáñez, Maria; Cadavid, Doris; Cabot, Andreu
Thermoelectricity is a key technology with the potential to improve the efficiency of energy conversion processes, which may strongly benefit from advances in the field of nanotechnology. Nanostructured materials are very appealing for thermoelectric applications, but the full development of their potential requires precise control of their properties at the nanoscale. Bottom-up assembly of nanoparticles provides access to a three-dimensional composition control at the nanoscale not attainable in any other technology. In particular, colloidal nanoheterostructures are especially interesting building blocks for the bottom-up production of functional nanomaterials. In the present work, we use PbTe@PbS core-shell nanoparticles as building blocks for the bottom-up production of PbTe-PbS nanocomposites. We used a ligand exchange strategy and a hot press process to promote the electrical conductivity of the nanocomposite and to increase its density. These two approaches allowed us to improve the performance of bottom-up assembled PbTe-PbS bulk nanostructured materials.